DEVELOPMENT OF SOCIAL STUDIES BASED WEBQUESTS FOR PRE-SERVICE TEACHERS IN COLLEGES OF EDUCATION IN SOUTHWESTERN, NIGERIA (2013)
Social studies is largely taught in schools using lecture method, which does not promote higher-order thinking skills. One of the ways by which students could be involved in meaningful learning and develop these skills is to integrate WebQuestsinto the teaching and learning process. Studies have been carried out on the effectiveness of WebQuests as teaching-learning tool. However, manyteachers do not possess the necessary skills to develop and use WebQuests in Nigerian classrooms. This could be attributed to the fact that teachers were not trained to use such technology. This study, therefore, developed WebQuests in social studies to train the pre-service teachers for the use of the tool in the teaching of social studies. It also examined the moderating effect of gender, attitude and prior knowledge of computer on pre-service teachers' WebQuests knowledge and skills as well as attitude to WebQuests. The study was executed in two phases. The first phase involved the designing of a WebQuest using Dodge WebQuest design model. The second phase employed case study research design. The study lasted 14 weeks. Participants comprised 152 second year pre-service teachers randomly selected from two colleges of education in the Southwest. The two colleges of education were purposively selected based on availability of functioning computer laboratories. Four instruments were used: Pre-service Teachers' Computer and WebQuests Literacy Test (r = 0.82), Pre-service Teachers' Attitude Towards Computer and WebQuests Questionnaire (r = 0.91), WebQuests Assessment Rubric (r = 0.88) and WebQuests Training Package. Seven research questions were answered and five hypotheses tested at 0.05 level of significance. Data were analysed using percentages, t-test and Analysis of Variance (ANOVA). The WebQuests were designed and developed through the following processes: selection of topic, writing of introduction, specifying the task, explaining the process, identifying resources, providing evaluation and writing of conclusion. The WebQuests development scores of pre-service teachers in Overall Aesthetic (66.8%); Introduction (79.8%); Task (56.6%); Process (59.1%); Resources (71.5%) and Evaluation (67.8%) at the post training level shows that they learn how to develop WebQuests. There was no significant difference among the pre-service teachers with low, average and high prior knowledge of computer in their post WebQuests development scores. There was no significant difference between male and female pre-service teachers in their post WebQuests development score. There was significant difference (t=12.78; df=302; p<0.05) between pre attitude (X ? = 64.73) and post attitude (X ? = 72.61) of pre-service teachers to WebQuests and computer. This implies that post attitude scores of participants were higher after the training. There was significant difference (t= -3.04; df= 150; p<0. 05) between the WebQuests of pre-service teachers in learning groups mean score (X ? = 33.73) and those that worked individually (X ? = 29.48). Pre-service social studies teachers in Colleges of Education were able to develop WebQuests after exposure to training. It is therefore recommended that training in WebQuests design and development should be given to pre-service teachers and that a curriculum be developed for this purpose.